GASEOUS RELEASES EVALUATION AND SAFETY PERFORMANCE IMPROVEMENT OF KARTINI RESEARCH REACTOR VENTILATION SYSTEM - Syarip; Edy Triono BS; Widyatmaka Susyanta; Hadi Kusuma (Ganendra: Majalah IPTEK Nuklir, 2026)
GASEOUS RELEASES EVALUATION AND SAFETY PERFORMANCE IMPROVEMENT OF KARTINI RESEARCH REACTOR VENTILATION SYSTEM. The safety performance of Kartini research reactor related to the gaseous releases to the environment has been evaluated. The research covers an evaluation and improvement on the ventilation system and analysis of gas releases dissipating from the reactor building. The method used is calculation of reactor source term and direct measurement of gas release from the reactor stack. The source term analysis showed that the fission product accumulated in the reactor core at the start of operation was 4.838 ´ 106 Ci, after of 5 hours operation it became 3.614 ´ 108 Ci, and after 24 hours decay, the fission product became 4.727 ´ 106 Ci. The N16 activity inside the reactor building is 4.1 ´ 10-10 μCi/cm3 and the Ar41 escaping to the atmosphere is 5.7 ´ 10-12 mCi/cm3, which is lower than limit value for radiation worker of 2 ´ 10-6 μCi/cm3. A sample case by using March 2009 data, the value of ground level concentration on variable distance x = 100 m to 5.000 m, was 9.726 ´ 10-19 rad/m3, rise up to 6.303 ´ 10-14 rad/m3 and tends to decrease to 1.598 ´ 10-15 rad/m3 at distance 5,000 m. Whiles the direct observation on the upper reactor stack show that the radiation exposure is 2.33 ´ 10-9 rad/s, exit velocity of gas from stack is 8 m/s, absolute temperature effluent of gas is 26.2 oC, and outlet diameter of stack, d = 1 m and actual stack height 31.75 m. Based on safety limit criteria from national regulation (BAPAETEN), the values of radiation exposure, ground level concentration combined with atmosphere stability and demography factor was very safe for the actual condition of Kartini reactor site.